Factors Associated with Exchange Transfusion among Severe Neonatal Jaundice in Malaysia - Wan Soliha Wan Mohd Hanafi; Wan Norlida Wan Ibrahim; Noran Hashim (Mashhad University of Medical Sciences, 2021)
Background: Neonatal jaundice may lead to a severe level if it is not well monitored. The long-term consequences of severe neonatal jaundice may result in devastating neurologic sequelae, including bilirubin encephalopathy and kernicterus. Exchange transfusion has remained the most effective modality for lowering serum bilirubin concentration. The present study aimed to determine the proportion and factors associated with exchange transfusion procedure among neonates with severe jaundice in Kelantan from 2015 to 2017. Methods: This cross-sectional study was carried out among neonates with severe jaundice in Kelantan between 2015 and 2017 using jaundice surveillance data from Kelantan Health State Department. Result: Out of the study subjects, 45 (19.7%) neonates had severe jaundice requiring an exchange transfusion procedure. From 2015 to 2017, the prevalence of severe neonatal jaundice requiring exchange transfusion raised from 17.0%-23.7%. The significant factors associated with exchange transfusion were neonatal infection, low birth weight, ABO blood group incompatibility, and maternal blood type O. Conclusion: As evidenced by the obtained results, exchange transfusion among severe neonatal jaundice in Kelantan followed an increasing trend within the study period. Associated factors leading to exchange transfusion among severe neonatal jaundice were neonatal infection, low birth weight, ABO incompatibility, and maternal blood type O. The recognition of these factors would be of great help in developing effective strategies aimed at the prevention of exchange transfusion procedure and its subsequent complications.